Prediction of macrophyte distribution: The role of natural versus anthropogenic physical disturbances. Issue 3 (13th May 2018) - Bertrin, Vincent; Boutry, Sébastien; Alard, Didier; Haury, Jacques; Jan, Gwilherm; Moreira, Sylvia; Ribaudo, Cristina
Abstract: Questions: Do natural and anthropogenic physical disturbances equally affect the distribution of aquatic plant communities? Can hydrodynamic and geomorphological features be used to predict the establishment of macrophyte communities at the shoreline scale? Locations: Two large, shallow lakes, southwest France. Methods: Based on field observations (vegetation occurrence and anthropogenic modifications of the shore) and data generated by a geographic information system (wave exposure, wave‐induced sediment re‐suspension, slope and land cover), we defined sites and community groups using cluster and indicator species analyses. The groups were then analysed by means of a statistical classifier (Random Forest). These different steps in data treatment enabled us to characterize the importance of each physical factor in determining macrophyte occurrence and distribution. As a result, a predictive map to forecast aquatic plant distribution at the shoreline scale was obtained. Results: Anthropogenic disturbances were less important parameters than natural physical variables in structuring the distribution of lakeshore macrophytes. Within natural factors, wave‐induced sediment re‐suspension and slope had the most impact; nevertheless, the presence of swimming areas seemed to have a strong impact on aquatic habitats, being correlated with the total absence of aquatic vegetation. The predictive map obtained through the model spatially defined the position and occurrence of suitable sites for the settlement of both invasive and rare and endangered species. Conclusions: In this study, natural disturbances play a major role in structuring aquatic plant distribution over physical anthropogenic factors. The model contributes to improving knowledge on plant communities with respect to local hydrodynamic and morphological features of lakeshores. Furthermore, the model provides a predictive map as a useful tool for the management of aquatic vegetation in temperate shallow lakes. Abstract : The diversity of aquatic plants inhabiting lakeshores originates from multiple interactions between natural and anthropic factors. By combining field data with modelling, we described the impact of local physical disturbances on the occurrence and location of ecological key‐species such as invasive hydrophytes and isoetids. The output predictive map constitutes a factual tool for vegetation management in shallow lakes.